Does an Abstract Weld Pool Visualization Help Novice Welders Assess the Performance of a Weldbot?. (September 2016) - Kent, Travis M.; Fu, Bo; Walls, Brittany D.; Seidelman, Will; Sublette, M.A.; Lee, Michael; Carswell, C. Melody; Yang, Ruigang
The domain of welding recently has seen the introduction of numerous potential aids to the practitioners who monitor welding robots ("welbots") or perform welds themselves. One such aid is the visual augmentation or visualization of particular weld pool parameters. The purpose of this study was to examine the potential effects of a simple, geometric weld pool visualization on the ability of novice welders to relate what they witnessed in welding videos to the completed welds on physically-present pipes (a situation awareness outcome). In addition to participants' accuracies on the situation awareness measure, perceived usability and subjective workload were also assessed. There was no reliable benefit for the augmented condition compared to the raw, unedited video condition. The results may indicate a task specificity for the type of augmentation utilized or possible limitations of the current rendering methods.